Knockout of NOS2 Promotes Adipogenic Differentiation of Rat MSCs by Enhancing Activation of JAK/STAT3 Signaling - Qin, Aiping; Chen, Sheng; Wang, Ping; Huang, Xiaotao; Zhang, Yu; Liang, Lu; Du, Ling-Ran; Lai, De-Hua; Ding, Li; Yu, Xiyong; Xiang, Andy Peng (Frontiers in Cell and Developmental Biology, 2021)
MSCs are a heterogeneous population of cells that possess multilineage differentiation potential and extensive immunomodulatory properties. In mice and rats, MSCs produce NO, as immunomodulatory effector molecule that exerts an antiproliferative effect on T cells, while the role of NO in differentiation was less clear. Here, we investigated the role of NO synthase 2 (NOS2) on adipogenic and osteogenic differentiation of rat MSCs. MSCs isolated from NOS2-/- and WT SD rats exhibited homogenous fibroblast-like morphology and characteristic phenotypes. However, after induction, adipogenic differentiation was found significantly promoted in NOS2-/- MSCs compared to WT MSCs, but not in osteogenic differentiation. Accordingly, qRT-PCR revealed that the adipogenesis-related genes PPAR-γ, C/EBP-α, LPL and FABP4 were markedly upregulated in NOS2-/- MSCs, but not for osteogenic transcription factors or marker genes. Further investigations revealed that the significant enhancement of adipogenic differentiation in NOS2-/- MSCs was due to overactivation of the STAT3 signaling pathway. Both AG490 and S3I-201, small molecule inhibitors that selectively inhibit STAT3 activation, reversed this adipogenic effect. Furthermore, after high-fat diet (HFD) feeding, knockout of NOS2 in rat MSCs resulted in significant obesity. In summary, NOS2 is involved in the regulation of rat MSC adipogenic differentiation via the STAT3 signaling pathway.